(untitled) (Stato, Chiese e pluralismo confessionale, 2011)
English alternate version of the paper “Libertà religiosa e federalismo in Europa: i precedenti della Repubblica Federale di Germania e della Confederazione elvetica” presented at the 2010 Meeting of ADEC (Associazione dei docenti di diritto ecclesiastico e canonico) that will be published on the review “Il Diritto ecclesiastico”. I want to thank Prof. Enrico Vitali – director of “Il Diritto ecclesiastico” - for the authorization to publish this English version. SUMMARY: 1. What do we mean about “Federalism”? – 2. Federalism and religions in Germany – 3. Federalism and religions in Switzerland.